PENGARUH PENGANGGURAN DAN KEMISKINAN TERHADAP KESEJAHTERAN MASYARAKAT DESA MEKAR JAYA DALAM PERSPEKTIF ISLAM - Bambang Kurniawan; Fathurrahman Fathurrahman; Endang Aprillia Dwi Rahayu (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the effect of unemployment and poverty on the welfare of the people of Mekar Jaya Village, this research is quantitative. The sample used was 170 respondents. Based on the research results, there is one variable that does not have a significant effect on the welfare of the people of Mekar Jaya Village, namely the poverty variable, while the unemployment variable has a positive and significant effect on the welfare of the people of Mekar Jaya Village. Simultaneously there is a significant influence between unemployment and poverty with an Adjusted R Square (R2) value of 0.408 or 40.8%, which means that the influence of the independent variable on the dependent variable gives an influence of 40.8% and the remaining 59.2% is influenced by other variables outside this research.